A Predictive Modelling Study for Using High Hydrostatic Pressure, a Food Processing Technology, for Protein Extraction - Altuner, Ergin Murat (Elsevier BV, 2016)
AbstractThe aim of this study is to fit a response model to one response, extracted protein concentration by using high hydrostatic pressure, a food processing technology, as a function of two particular controllable factors of extraction procedure. These factors are “pressure” (applied in MPa) and the “extraction solvent”. Data were taken from a previously published data, where the minimum and maximum values chosen for pressure were 100MPa and 300MPa with a center point of 200MPa. The solvents were PBS, TCA-Acetone and Tris-HCl. Protein concentration values were the mean values of 3 replicates.Firstly, a regression statistics were conducted by the data mentioned above to identify coefficients for intercept, pressure and solvents. The coefficients for intercept, pressure and solvents were identified as 34.29753333, 0.008442 and 0.85425 respectively with p-values of 0.03 for pressure and 0.10 for solvents.A predictive analysis model was fitted to the protein concentration response by using the predictive analysis model proposed with the analysis conducted.
Keywords: protein extration; High hydrostatic pressure; 2. Zero hunger